Pengaruh Perawatan Kulit Wajah Terhadap Kepercayaan Diri Remaja Putri di Kelas XI Jurusan Tata Kecantikan SMKN 27 Jakarta: Penelitian - Saidah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Self-confidence means believing in yourself how you act, feel, and think. It comes from within and helps you do things based on your own abilities, making life feel more meaningful. For teenage girls, looking good physically can help boost their self-confidence. One way to do that is by taking care of their facial skin. This study looked at how much facial skincare affects the self confidence of 11th-grade girls in the Beauty Department at SMKN 27 Jakarta. The researchers used a questionnaire to collect data from 59 students. There were 18 questions about facial skincare and 30 questions about self-confidence. After analyzing the data using a simple statistical test (called linear regression), the results showed a significance value of 0.011, which is less than 0.05. This means the result is important and not just a coincidence. Another test (t-test) showed that the calculated value (6.627) was higher than the required value (2.002). So, the conclusion is that facial skincare really does have a positive effect on self-confidence.